Determinant Akuntabilitas Pengelolaan Keuangan Dana Bantuan Operasional Sekolah Pada UPT SPF SMP Negeri 1 Batang Kuis: Penelitian - Riki Novita Dewi Harahap; Reza Hanafi Lubis (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The purpose of this study was to determine the effect of human resource quality (HR), accounting information systems, internal control, transparency together on the accountability of the management of School Operational Assistance Funds at UPT SPF SMP Negeri 1 Batang Kuis. Data collection techniques used in this study were questionnaires, observations, interviews, and documentation. This study used multiple linear regression analysis. The results showed that Human Resource Quality had a positive and significant effect on Accountability, Accounting Information Systems had a positive and significant effect on Accountability, Internal Control had a positive and significant effect on Accountability, Transparency had a positive and significant effect on Accountability, and human resource quality, accounting information systems, internal control and transparency together had an effect on Accountability. The quality of human resources, accounting information systems, internal control and transparency have a strong relationship with Accountability, which is 0.753. Or the quality of human resources, accounting information systems, internal control and transparency is 75.3%. while the remaining 24.7% is influenced by other factors not included in this study.